Analytical prediction of time-dependent behavior for tunneling-induced ground movements and stresses subjected to surcharge loading based on rheological mechanics. (January 2021) - Zhang, Zhiguo; Huang, Maosong; Pan, Yutao; Jiang, Kangming; Li, Zhenbo; Ma, Shaokun; Zhang, Yangbin
Abstract: Current analytical solutions on the ground movements and stresses induced by shield tunneling in soft soils are generally based on the instantaneous excavation behavior. Furthermore, previous studies seldom took account of the influence of surcharge loading during tunnel excavation process. This paper introduces a complex variable analytical solution to estimate the deformation and stress of surrounding soils caused by shield tunneling subjected to surcharge loading considering the soil rheological mechanisms. The non-uniform convergence deformation boundary is adopted at the tunnel opening and the Boltzmann viscoelastic model is employed in the time-domain solution so as to consider the displacement controlled boundary and the rheological effects. The accuracy of complex variable time-dependent solution is then verified by comparisons with in-situ observed data, and good consistency is obtained. Finally, the parametric analyses are performed to evaluate the influence of correlative coefficients in Boltzmann viscoelastic model and paramount factors of surcharge loading on the feedback around tunneling. The ratios of the peak values of final surface settlements induced by tunneling in viscoelastic soils to those in elastic soils in the initial period vary approximately from 40% to 120%. The soil stresses around the tunnel increase about 50% significantly over time.